Income shares, wealth and growth - Piero Ferri; Anna Maria Variato (EconomiA, 2016)
The paper analyzes the relationship between income shares, wealth and growth in an environment where positional goods are taken into account and rent is generated. This hypothesis, which is a macro engine for inequality, creates a gap between profit share and property share and implies a clear-cut distinction between capital and wealth. The interactions between these aspects are studied in a medium-run growth model led by aggregate demand, where monetary aspects also matter. The results of the dynamic analysis, obtained by means of simulations, are in keeping with some recent stylized facts. Furthermore, the model generates bounded dynamics, where the co-movements between variables are more complex than those obtained in the recent literature. At the same time the disequilibrium processes can create a link between medium-run considerations and a more long-run perspective. – – Esse artigo analisa a relaç\~ao entre participaç\~ao na renda, riqueza e crescimento em um ambiente em que bens de `status' s\~ao levados em consideraç\~ao e renda é gerada. Essa hipótese, que é uma macro motor de desigualdade, cria um hiato entre participaç\~ao dos lucro e participaç\~ao de propriedades e implica em uma distinç\~ao clara entre capital e riqueza. As interaç\~oes entre esses aspectos s\~ao estudados em um modelo de crescimento de médio prazo impulsionado pela demanda agregada, onde aspectos monetários s\~ao importantes também. Os resultados dessa análise dinâmica, obtidos por meio de simulaç\~oes, est\~ao de acordo com alguns fatos estilizados. Além disso, o modelo gera uma dinâmica restrita, onde o co-movimento entre as variáveis s\~ao mais complexos do que aqueles encontrados na literatura recente. Ao mesmo tempo, o processo de desequilíbrio pode criar uma ligaç\~ao entre consideraç\~oes de médio-prazo e uma perspectiva de mais longo prazo.
Keywords: D31; E; E2; O4; 330; Property and profit share; Positional goods; Private wealth; Inequality; Demand-led growth; Limit cycles